Identification of α-Amyrin 28-Carboxylase and Glycosyltransferase From Ilex asprella and Production of Ursolic Acid 28-O-β-D-Glucopyranoside in Engineered Yeast - Ji, Xiaoyu; Lin, Shumin; Chen, Yuanyuan; Liu, Jiawei; Yun, Xiaoyun; Wang, Tiancheng; Qin, Jialiang; Luo, Chaoquan; Wang, Kui; Zhao, Zhongxiang; Zhan, Ruoting; Xu, Hui (Frontiers in Plant Science, 2020)
Ilex asprella is a medicinal plant that is used extensively in southern China. The plant contains ursane-type triterpenoids and triterpenoid saponins which are known to be responsible for its pharmacological activities. Previously, a transcriptomic analysis of I. asprella was carried out and the gene IaAS1, which is important in the formation of the core structure α-amyrin, was identified. However, the genes related to the subsequent derivatization of the core structures of the triterpenoid remain largely unknown. Herein, we describe the cloning and functional characterization of an amyrin 28-carboxylase IaAO1 (designated as IaCYP716A210 ) and a glycosyltransferase IaAU1 (designated as UGT74AG5), based on transcriptomic data. The expression of IaAO1 in an α-amyrin producing yeast strain led to the accumulation of ursolic acid. An enzyme assay using recombinant protein IaAU1 purified from E. coli revealed that IaAU1 can catalyze the conversion of ursolic acid to ursolic acid 28-O-β-D-glucopyranoside. IaAU1 has regiospecificity for catalyzing the 28-O-glucosylation of ursane-/oleanane-type triterpene acids, as it can also catalyze the conversion of oleanolic acid, hederagenin, and ilexgenin A to their corresponding glycosyl compounds. Moreover, co-expression of IaAO1 and IaAU1 in the α-amyrin-producing yeast strain led to the production of ursolic acid 28-O-β-D-glucopyranoside, although in relatively low amounts. Our study reveals that IaAO1 and IaAU1 might play a role in the biosynthesis of pentacyclic triterpenoid saponins in I. asprella and provides insights into the potential application of metabolic engineering to produce ursane-type triterpene glycosides.